1979
DOI: 10.1111/j.1748-1716.1979.tb06389.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis in the monkey: hemodynamics and blood flow distribution

Abstract: Aggregate anaphylaxis was induced in eight ovalbumin-sensitized monkeys (Macaca irus). Hemodynamics, blood flow distribution and myocardial performance were studied. Following challenge, severe circulatory shock developed. Systemic arterial and left atrial pressures decreased and pulmonary arterial and right atrial pressures increased. There was a tenfold increase in pulmonary vascular resistance, and cardiac output was markedly reduced (-75%). A redistribution of the blood flow to vital organs (brain, heart a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Immune complexes cause thrombocytopenia in primates by cross-linking of FcgRIIa on the platelet surface, resulting in activation. Platelet activation can result in pulmonary thromboemboli, complement activation, and release of vasoactive amines that cause pulmonary venoconstriction (Del Conde et al 2005;Hedin and Smedegard 1979;Radegran, Drugge, and Olsson 1974;Radegran and McAslan 1972;Revenas, Smedegard, and Saldeen 1980;Smedegard, Revenas, and Arfors 1979).…”
Section: Hypersensitivity Reactionsmentioning
confidence: 99%
“…Immune complexes cause thrombocytopenia in primates by cross-linking of FcgRIIa on the platelet surface, resulting in activation. Platelet activation can result in pulmonary thromboemboli, complement activation, and release of vasoactive amines that cause pulmonary venoconstriction (Del Conde et al 2005;Hedin and Smedegard 1979;Radegran, Drugge, and Olsson 1974;Radegran and McAslan 1972;Revenas, Smedegard, and Saldeen 1980;Smedegard, Revenas, and Arfors 1979).…”
Section: Hypersensitivity Reactionsmentioning
confidence: 99%
“…Their studies, however, focused on functional changes of respiratory and hemodynamic parameters associated with anaphylactic shock, and detailed descriptions of blood flow distribution are lacking. In contrast, Smedegard et al extensively examined anaphylaxis-induced alterations in hemodynamics and blood flow distribution in a monkey model (25,26). They demonstrated that animals developed a severe state of shock within two minutes following the antigen challenge, with high pulmonary vascular resistance, low cardiac output, and profound hypotension.…”
Section: Discussionmentioning
confidence: 86%
“…reported that monkeys with severe anaphyalactic shock tended to have higher systemic resistance than monkeys with mild anaphylactic shock. Also, Srnedegard et al 7 observed that total peripheral resistance increased 1.5 times in anaphylactic shock in the monkey. In humans, there are some reports that systemic vascular resistance decreases'< P or increasesv'-!".…”
Section: Discussionmentioning
confidence: 94%